59.7k views
4 votes
If B = k – 5k^2 – 1 and C = k – 2k^2, find an expression that equals 2B + 3Cin standard form.

1 Answer

4 votes

Answer


-16k^2+5k-2

Step-by-step explanation

• Given


B=k-5k^2-1
C=k-2k^2

Expression:


2B+3C

• Procedure

Replacing the values of B and C in the expression:


=2(k-5k^2-1)+3(k-2k^2)

Simplifying the expression:


=2k-10k^2-2+3k-6k^2

Adding similar terms:


=-10k^2-6k^2+2k+3k-2
=-16k^2+5k-2

User Scott Jibben
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.